DNA immunization with a herpes simplex virus 2 bacterial artificial chromosome() - Meseda, Clement A. (Virology, 2004)
Construction of a herpes simplex virus 2 (HSV-2) bacterial artificial chromosome (BAC) is described. BAC vector sequences were inserted into the thymidine kinase gene of HSV-2 by homologous recombination. DNA from cells infected with the resulting recombinant virus was transformed into E. coli, and colonies containing the HSV-2 BAC (HSV2-BAC) were isolated and analyzed for the expected genotype. HSV2-BAC DNA was infectious when transfected back into mammalian cells and the resulting virus was thymidine kinase negative. When used to immunize mice, the HSV2-BAC DNA elicited a strong HSV-2 specific antibody response that was equal to or greater than live virus immunization. Further, HSV2-BAC immunization was protective when animals were challenged with a lethal dose of virus. The utility of the HSV2-BAC for construction of recombinant virus genomes was demonstrated by elimination of the HSV-2 glycoprotein D (gD) gene. A recombinant HSV-2 BAC with the gD gene deleted was isolated and shown to be incapable of producing infectious virus following transfection unless an HSV gD gene was expressed in a complementing cell line. Immunization of mice with the HSV2 gD-BAC also elicited an HSV-2 specific antibody response and was protective. The results demonstrate the feasibility of DNA immunization with HSV-2 bacterial artificial chromosomes for replicating and nonreplicating candidate HSV-2 vaccines, as well as the utility of BAC technology for construction and maintenance of novel HSV-2 vaccines. The results further suggest that such technology will be a powerful tool for dissecting the immune response to HSV-2.